2017
DOI: 10.1111/ejss.12441
|View full text |Cite
|
Sign up to set email alerts
|

Response of soil microbial community structure to increased precipitation and nitrogen addition in a semiarid meadow steppe

Abstract: Additions of nitrogen (N) and water might have an interactive effect on the structure of the soil microbial community. The effects and importance of a fluctuating natural precipitation regime on the soil microbial community in a semiarid meadow steppe are very variable and less well known. On a Stipa baicalensis Rosh. meadow steppe, we used phospholipid fatty acid (PLFA) analysis to evaluate the effects of increased precipitation, addition of nitrogen and precipitation regime in regulating the structure of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 42 publications
0
15
0
Order By: Relevance
“…Soil water content and soil pH were the key factors to regulate soil microbial community structure, function, and soil carbon process [54]. The result showed that thinning treatment increased soil water content.…”
Section: Correlation Between Soil Microbial Community Structure and Smentioning
confidence: 97%
See 1 more Smart Citation
“…Soil water content and soil pH were the key factors to regulate soil microbial community structure, function, and soil carbon process [54]. The result showed that thinning treatment increased soil water content.…”
Section: Correlation Between Soil Microbial Community Structure and Smentioning
confidence: 97%
“…It was suggested that there were strong correlations between soil pH and microbial community to control soil carbon turnover. The previous study theorized that soil physicochemical properties and microbiological diversity contributed to carbon turnover and transformation [54]. After thinning treatment, the variation in soil pH and soil water content influenced soil microbial function relating to carbon decomposition, which was regulated by soil microbial community structure, and finally affected soil carbon properties.…”
Section: Effects Of Soil Ph Soil Water Content and Microbial Factormentioning
confidence: 98%
“…Bi et al (2012) reported the interactive effects of water and N addition on gram negative/gram positive bacteria and the ratio of fungal to bacterial PLFA in a semiarid steppe. In addition, the response of microbial communities to precipitation changes and N deposition may depend on the inter-annual variation of the climate (Sun et al, 2014), variation in inter-annual precipitation (Sun et al, 2017), and vegetation type (Khalili et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Although many studies had been conducted to evaluate the effects of water and nitrogen fertilizer addition on soil organism community, many variations and inconsistencies can be found in the literature (Melguizo-Ruiz et al, 2017;Sun et al, 2017). Although many studies had been conducted to evaluate the effects of water and nitrogen fertilizer addition on soil organism community, many variations and inconsistencies can be found in the literature (Melguizo-Ruiz et al, 2017;Sun et al, 2017).…”
mentioning
confidence: 99%
“…Changes in water and nitrogen fertilizer addition may affect soil organism communities through different mechanisms. Although many studies had been conducted to evaluate the effects of water and nitrogen fertilizer addition on soil organism community, many variations and inconsistencies can be found in the literature (Melguizo-Ruiz et al, 2017;Sun et al, 2017). For example, elevated water addition increased soil fungi and decreased soil bacteria, while increased nitrogen fertilizer addition had the opposite effects because water addition led to significant changes in soil characteristics (Ma et al, 2016).…”
mentioning
confidence: 99%